2023
DOI: 10.5144/0256-4947.2023.50
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of empagliflozin: a “real-world” experience from Saudi Arabia

Abstract: BACKGROUND: Sodium-glucose cotransporter 2 (SGLT2) inhibitors are new agents for treating type 2 diabetes. In addition to the glycemic benefits, these agents provide cardiorenal protection in patients with diabetes and without diabetes. There is consistent evidence that these agents increase the risk of genitourinary infections and dehydration, but randomized controlled trials have not included patients from the Middle East. OBJECTIVES: Determine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…In keeping with previous reports from Saudi Arabia,[ 25 ] the present study showed a slightly reduced MAP after initiating SGLT2 inhibitors. Some international studies have similarly reported a reduction in arterial pressure (AP) after treatment with SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In keeping with previous reports from Saudi Arabia,[ 25 ] the present study showed a slightly reduced MAP after initiating SGLT2 inhibitors. Some international studies have similarly reported a reduction in arterial pressure (AP) after treatment with SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous reports from Saudi Arabia,[ 25 ] our study demonstrated that SGLT2 inhibitors resulted in a better control of type 2 DM in Saudi patients. However, the study also confirms the antihyperglycemic effect of a different SGLT2 inhibitor in Saudis with type 2 DM.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations